«PHILEO» AS RECIPROCAL LOVE - Ільїн, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of philosophy existence in the modern world is regarded in the article. The estimation of philosophy and its characteristics as the attribute of man’s being are given a special consideration.